Pengembangan Muatan Pendidikan Lingkungan Sebagai Kerangka Pemahaman Pelestarian Kawasan - Rita Sulastini; Okke Rosmaladewi; Erry Mustariani (Dikmas: Jurnal Pendidikan Masyarakat dan Pengabdian, 2023)
Environmental education in principle focuses on knowledge which emphasizes about interaction and linkages between humans and the environment as a life support. So far, environmental education learning is more about the introduction of objects and environment element as an ecosystem. However, it’s not until of environmental education substance specifically, according as a fact from each area. Therefore, learning on environmental education is needed and its branch of knowledge. This aim is that with the guidance from the lectures as a learning facilitators, student know, learn and able to analyze the environmental education content for every single object which discovered, so that they can provide concrete solutions to optimizing the area. The locus study is Gunung Puntang Forest Area, Campakamulya Village, Cimaung, Banjaran District, Bandung Regency West Java. This research used naturalstic qualitative method, which the researcher directly involved start from submission process, visits, observations and participated in all activities in natural setting. By using environmental education theory and environmental policy, environmental education is studied based on : 1) based on nature envirenmont, 2) based on spaceand place, 3) basedon social and culture, 4) based on built environment, and 5) based on spesific environment. Therefore environmental education must be taught at every level education system and related instituions because it is charged to maintain living environmental order.